Irgm1 promotes M1 but not M2 macrophage polarization in atherosclerosis pathogenesis and development. (August 2016) - Fang, Shaohong; Xu, Yanwen; Zhang, Yun; Tian, Jiangtian; Li, Ji; Li, Zhaoying; He, Zhongze; Chai, Ruikai; Liu, Fang; Zhang, Tongshuai; Yang, Shuang; Pei, Chunying; et al.
Abstract: Background and aims: Atherosclerosis is a chronic inflammatory vascular disease related to macrophages uptake of low-density lipoprotein and their subsequent transformation into foam cells. M1 (inflammatory)/M2 (anti-inflammatory) balance was suggested to impact disease progression. In this study, we investigated whether the immunity related GTPase (Irgm1) regulates macrophage polarization during atherosclerosis development. Methods: We used apolipoprotein E ( ApoE ) knockout and Irgm1 haplodeficient mice and induced atherosclerosis with high-cholesterol diet for the indicated months. Atherosclerotic arteries were collected from patients undergoing vascular surgery, to determine the lesional expression of Irgm1 and distribution of M1/M2 populations. Results: Our results showed that IRGM / Irgm1 expression was increased in atherosclerotic artery samples (1.7-fold, p =0.0045) compared with non-atherosclerotic arteries, which was consistent with findings in the murine experimental atherosclerosis model (1.9-fold, p =0.0002). IRGM / Irgm1 expression was mostly found in lesional M1 macrophages. Haplodeficiency of Irgm1 in ApoE −/− mice resulted in reduced infiltrating M1 macrophages in atheroma (94%, p =0.0002) and delayed development of atherosclerotic plaques. In vitro experiments also confirmed that Irgm1 haplodeficiency reduced iNOS expression of polarized M1 macrophages (81%, p =0.0034), with negligible impact on the M2 phenotype. Moreover, we found that Irgm1 haplodeficiency in mice significantly reduced expression level of M1 function-related transcription factors, interferon regulatory factor ( Irf ) 5 and Irf8, but not Irf4, an M2-related transcription factor. Conclusions: This study shows that Irgm1 / IRGM participates in the polarization of M1 macrophage and promotes development of atheroma in murine experimental atherosclerosis. Highlights: Irgm1 promotes murine M1 macrophage polarization. Irgm1 does not affect M2 macrophage polarization. Irgm1 haplodeficiency decreases the level of M1-related transcription factors Irf5 and Irf8. Irgm1 haplodeficiency exerts minimal effect on M2-related transcription factor Irf4. Irgm1 haplodeficiency renders ApoE −/− mice resistant to atherosclerosis.